Caractérisation des systèmes de production et des ressources fourragères dans un terroir test de la zone soudanienne du Burkina Faso - H.O. Sanon; M. Savadogo; H.H. Tamboura; B.A. Kanwé (VertigO)
The Sudanian zone of Burkina Faso is considered as the area with the highest agro-sylvo-pastoral potential of the country. The aim of this study was to characterize the production systems and the status of forage resources from two contiguous land sites in the Southwest of the country. The methodology consisted of formal surveys with farmers and field inventories. The characterization of production systems allowed to distinguish four groups of producers which differ by their social status, resources and productions strategies used. The first two groups (Lobi) are indigenous landowners practicing traditional shifting cultivation, whereas the other two groups consist of non-native (Fulani and Mossi) exploit essentially borrowed land permanently. They are better off in agricultural equipment and use some inputs (organic and mineral fertilizer) to improve production. In general, there is not a good integration of crops and livestock in indigenous producers, while non-native producers are investing more. The mapping of the study area allowed to identify five landscapes units that differ in the appearance of vegetation and land use: the shrubby savanna, sparse woody savanna, dense woody savanna, riparian vegetation and cropland areas. Phyto-sociological studies in these units (except cropland) results in a flora of 95 herbaceous species and 55 woody species. Herbaceous biomass ranged from 2.9 tons / ha DM in the dense savannas to 10.6 tons / ha in riparian formations, allowing a carrying capacity of 0.45 to 1.63 TLU / ha / year. The contribution of crop residues is substantial and could support additional load of 1300 TLU / year and with slightly higher nutritional value than pastures in dry season. In general, the feed balance of the area is positive, confirming the important forage availability, with however constraints for sustainable exploitation.